AUGMENTED REALITY BOOK PENGENALAN KONSEP DAN PERLENGKAPAN SUBAK - I Gede Merta; Padma Nyoman Crisnapati; I Made Gede Sunarya; I Gede Mahendra Darmawiguna (Universitas Pendidikan Ganesha, 2015)
Subak is one of the traditional institutional asset which proved to be effective to support agriculture and rural development in Bali. As its uniqueness, this socio-agrarian-religious organizations is able to attract the tourists to visit Bali. Not only tourists, the experts of agriculture and rural development; social and anthropology scientists; as well as the observer of technical irrigation also not miss to make Subak as their research object. The positive image of Subak is getting increased after it crowned as a world cultural heritage by UNESCO on June 29, 2012. Nevertheless, the younger generation of Bali seemed still antipathy towards sustainability of Subak. That circumstance was trigger the birth of this study that aimed to design and implement the application of introduction to the concept and equipments of Subak by utilizing augmented reality technology.The research that combines technology into the framework of cultural preservation like this is using research and development method.Meanwhile, the application of introduction to the concept and equipments of Subak that generated from this study was developed with the waterfall model. There are some tools that utilized to develop this application, such as Blender, Vuforia and Unity 3D.The output of this research are a book and an android application. This android application will help us to display the 3D objects of the concept and equipments of Subak followed by the narration audio in English as an additional feature that distinguishes this book with other conventional books. Based on the test results, this application will only well-running on mobile devices that carry the Android operating system at least version 2.2. The entire additional features such as navigation buttons and narration audio run properly on all mobile devices that are used in the testing.